Knowledge transfer in higher education : collaboration in the arts and humanities - Mooney Smith, Lisa, 1966- (Palgrave Macmillan, 2012)
"Presents years of close observation of research and knowledge transfer practices in a UK university. It attempts to contextualise knowledge transfer within the arts and humanities, as well as situate learning about the reception and adoption of knowledge transfer by the individual scholar and the organization in which they operate. Within this context, little has been written explicitly about the character of these disciplines, and particularly their close relationship to current knowledge transfer challenges. The study suggests that the culmination of this knowledge might offer a useful framework for considering how knowledge transfer occurs in complex teams, and at the same time how it might act as a tool with which knowledge transfer players and practices might be better observed. In presenting a new observational framework, the author suggests that the current preoccupation with impacts might be better understood at a more intimate level, thereby exposing vital emergent impacts during the collaborative research process."--Publisher description.